Aggressive containment, suppression, and mitigation of covid-19: lessons learnt from eight countries. (28th November 2021) - Wu, Shishi; Neill, Rachel; De Foo, Chuan; Chua, Alvin Qijia; Jung, Anne-Sophie; Haldane, Victoria; Abdalla, Salma M; Guan, Wei-jie; Singh, Sudhvir; Nordström, Anders; Legido-Quigley, Helena
Abstract : Shishi Wu and colleagues examine three distinct response strategies for covid-19 in eight countries and argue that aggressive containment is the optimal approach to limiting loss of lives and livelihoods and achievable in the absence of vaccines and effective therapies